First collection of Pinnasa volubilis (Loasaceae) in Lanín National Park (Semiárida, 2021)
In this note the first collection of Pinnasa volubilis in the Lanín National Park is reported, a species cited for the first time for Argentina in 2019 in the northcentral province of Neuquén.
Keywords: Flora; Lanín National Park; Loasaceae